A Queer Reading of Nawabi Architecture and the Colonial Archive - Mithal, Sonal (Taylor & Francis, 2025)
A Queer Reading of Nawabi Architecture and the Colonial Archive explores the architectural production of nawabs Asaf-ud-Daula and Wajid Ali Shah and reveals the colonial bias against queer expression. It offers methods of using queer strategies to read archival evidence against the grain and rewrite erased, overlooked, and suppressed histories. The book provides its readers a unique queer postcolonial architectural history of Lucknow from 1775–1857. It highlights the nawabs’ non-normative expressions, which not only offered a fierce resistance to the colonial enterprise but also were instrumental in furthering Lucknow as a cultural center. It simultaneously extracts parameters from queer studies and redefines them to illustrate ways in which queer architecture can be characterized. It reconstructs the footprint of nawabi architecture erased by the colonial enterprise and places it back on map—an exercise not undertaken meticulously until now. A Queer Reading of Nawabi Architecture and the Colonial Archive is intended for scholars and students of queer studies, postcolonial studies, architectural history, and the global south, as well as the citizens of Lucknow.